Problems of organization and maintenance of financial accounting in the conditions of implementation of the latest methods and tools - Khomiak, N.; Хомяк, Н.; Petchenko, M. V.; Петченко, М. В.; ORCID: http://orcid.org/0000-0003-1104-5717; Yarmoliuk, O.; Ярмолюк, О.; Viter, S.; Вітер, С.; Dmytrenko, O.; Дмитренко, О. (Фінансово-кредитна діяльність: проблеми теорії і практики. – 2022. – Т. 6 (47). – С. 88-98, 2022)
Досліджено існуючі проблеми бухгалтерського фінансового обліку, а також окреслено нові виклики сучасності, що несуть і загрози, і можливості. Зазначено, що частина існуючих проблем бухгалтерського фінансового обліку має бути вирішена на державному рівні шляхом унесення змін до законодавчої бази. Інша частина проблем може бути розв’язана через запровадження новітніх технологій. Наголошено, що неефективне та невідповідне застосування нових технологій може призвести не до покращення організації бухгалтерського обліку, а до появи нових проблем. Напрямом подальших досліджень може бути вивчення досвіду інших країн щодо гармонізації МСФЗ з національними стандартами звітності та використання новітніх технологій, а також пошук шляхів адаптації цього досвіду до українських реалій.

The relevance of the research topic is related to the emergence of a number of new challenges for the financial accounting system along with unresolved problems that have existed for a long time. The purpose of the research is to study the existing problems of financial accounting and outline the new challenges of modernity, which carry both threats and opportunities. The following scientific methods were used in the article: analysis and synthesis, generalization, the method of establishing causal relationships, the method of economic and statistical analysis, and graphic methods. As a result of the research, a number of problems were identified, which were defined as "traditional", that is, those that have existed for a long time, as well as a group of problems characterized as "new challenges", which are mostly associated with the emergence of innovative accounting tools. "Traditional" problems were considered in general and in terms of individual directions. The characteristics of the new challenges consist in the disclosure of the most popular modern financial accounting tools and the risks associated with their use. As a result of the study, it is stated that part of the existing problems of accounting and financial accounting should be solved at the state level by making changes to the legislative framework. Another part of the problems can be solved through the introduction of the latest technologies. It is emphasized that inefficient and inappropriate application of new technologies may not lead to the improvement of financial accounting organization, but to the appearance of new problems. The direction of further research may be to study the experience of other countries in harmonizing IFRS with national reporting standards and the use of the latest technologies, as well as in finding ways to adapt this experience to Ukrainian realities.

Исследованы существующие проблемы бухгалтерского финансового учета, а также очерчены новые вызовы современности, несущие и угрозы, и возможности. Указано, что часть существующих проблем бухгалтерского финансового учета должна быть решена на государственном уровне путем внесения изменений в законодательную базу. Другая часть проблем может быть решена через внедрение новейших технологий. Отмечено, что неэффективное и неподходящее применение новых технологий может привести не к улучшению организации бухгалтерского учета, а к появлению новых проблем. Направлением дальнейших исследований может быть изучение опыта других стран по гармонизации МСФО с национальными стандартами отчетности и использования новейших технологий, а также поиск путей адаптации этого опыта к украинским реалиям.
Проблеми організації та ведення фінансового обліку в умовах імплементації новітніх методів та інструментів
Khomiak, N. Problems of organization and maintenance of financial accounting in the conditions of implementation of the latest methods and tools / Nataliia Khomiak, Maryna Petchenko, Olena Yarmoliuk, Svitlana Viter, Olga Dmytrenko // Фінансово-кредитна діяльність: проблеми теорії і практики. – 2022. – Т. 6 (47). – С. 88-98. - DOI: https://doi.org/10.55643/fcaptp.6.47.2022.3914.
Хомяк , Н., Петченко , М., Ярмолюк , О., Вітер , С., & Дмитренко, О. (2022). ПРОБЛЕМИ ОРГАНІЗАЦІЇ ТА ВЕДЕННЯ ФІНАНСОВОГО ОБЛІКУ В УМОВАХ ІМПЛЕМЕНТАЦІЇ НОВІТНІХ МЕТОДІВ ТА ІНСТРУМЕНТІВ. Financial and Credit Activity Problems of Theory and Practice, 6(47), 88–98. https://doi.org/10.55643/fcaptp.6.47.2022.3914.
Keywords: Економіка. Економічні науки. Економічна безпека. Economics. Economic Security. Экономика. Экономические науки. Экономическая безопасность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; бухгалтерський фінансовий облік; accounting and financial accounting; цифровізація; digitization; цифровизация; новітні технології; new technologies; новейшие технологии; блокчейн; blockchain; big data; великі дані; хмарні технології; cloud technologies; облачные технологии; штучний інтелект; artificial intelligence; искусственный интеллект; Техніка. Технічні науки. Machinery. Engineering. Техника. Технические науки; publikatsii u WoS